The emergence of French-speaking literature in the colonized peripheries: Convergences and Divergences - (:unkn) unknown (My University, 2018)
In the context of the French-speaking African continent, North Africa (the Maghreb) stands out from sub-Saharan Africa. These two Francophone spaces stand out from each other, indeed, not only by certain literary schools, but also by the fact that the transition from pre-colonial literatures to French-language literature involves, in both contexts, different issues. On the other hand, in the Middle East (the Mashreq), the analytical approach takes another path. In Middle Eastern societies, the social and economic, the linguistic and the political, the religious and the ethnic are mixed. By making use of a historical reading of the beginnings of Francophone literatures in these three cultural areas, can we trace the divergences and convergences that have distinguished them so much from each other?
Keywords: African Research